Implementation of the Project Based Learning (PjBL) Learning Model to Increase Student Learning Activeness in Civics Class XI MAN 1 Deli Serdang Academic Year 2022/2023 - Adinda Siti Rahmah Sirait; Disna Anum Siregar (PT Inovasi Pratama Internasional, 2023)
This research aims to determine the application of the Project Based Learning (PjBL) learning model to increase student learning activity in the PPKn class XI MAN 1 Deli Serdang academic year 2022/2023. This type of research is Classroom Action Research (PTK) which consists of two cycles with Kemmis and Mc Taggart research designs. The action research flow consists of four stages, namely planning, action, observation, and reflection. The research subjects were 35 students in class XI MAN 1 Deli Serdang with a composition of 20 female students and 15 male students. To obtain this field data, the author used data collection techniques in the form of observation, interviews and documentation. The results of this research show that the application of the Project Based Learning (PjBL) learning model can increase student learning activity in class XI PPKn subjects at MAN 1 Deli Serdang for the 2022/2023 academic year. What can be seen from the results of the teacher observation sheet in cycle I only reached 55% and the results of the student observation sheet reached 51.4%, which was in the less active category. In cycle II, the results of the teacher observation sheet had reached 82.5% and the results of the student observation sheet had reached 82.8%, falling into the very active category and had met the criteria for successful action. Based on the research results, it can be concluded that using the Project Based Learning (PjBL) learning model can increase student learning activity in class XI PPKn subjects at MAN 1 Deli Serdang for the 2022/2023 academic year.